2017
DOI: 10.1093/mmy/myx090
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Aspergillus nidulans α-1,3-glucan synthase increases cellular adhesion and causes cell wall defects

Abstract: Alpha-1,3-glucan is important for pathogenesis by Aspergillus fumigatus, but the mechanism is unclear since the deletion has no hyphal phenotype. We dissected the roles of A. nidulans α-1,3-glucan in constitutive overexpression strains. Constitutive high-level α-1,3-glucan synthase activity increased hyphal wall thickness, but colonies grew slowly and sporulated poorly and had much higher adhesion to hydrophobic materials. Surprisingly, this overexpression strain formed a biofilm-like structure in plastic cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…If the amounts of the polysaccharide were low, no cleistothecia were formed ( Zonneveld, 1972 ). Another example of wall alterations by the levels of α 1,3 glucan was the observation that overexpresion of the synthesizing enzyme increased cellular adhesion and wall defects of A. nidulans ( He et al, 2018 ).…”
Section: Fungal Wall Alpha Glucansmentioning
confidence: 99%
“…If the amounts of the polysaccharide were low, no cleistothecia were formed ( Zonneveld, 1972 ). Another example of wall alterations by the levels of α 1,3 glucan was the observation that overexpresion of the synthesizing enzyme increased cellular adhesion and wall defects of A. nidulans ( He et al, 2018 ).…”
Section: Fungal Wall Alpha Glucansmentioning
confidence: 99%
“…A. nidulans is phylogenetically related to other species of economic importance, including A. niger and A. oryzae and clinically relevant species such as A. fumigatus (Galagan et al, 2005). Previous studies have described the A. nidulans adhesion in hydrophobic surfaces and their biofilm development, both of which are critical for the virulence of Aspergillus species (Shukla et al, 2017;He et al, 2018;Kadry et al, 2018;Lingo et al, 2021). Kadry et al (2018) used scanning electron microscopy (SEM) and found that A. nidulans strains (ΔgmtA and ΔgmtB) did not produce guanosine diphosphate mannose transporter (GMT), a transporter required for mannosylation of galactomannan and mannoproteins, exhibited smaller colony size, reduced sporulations, increased hyphal width and decreased based cell length.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the spores of A. nidulans ΔgmtA had a rougher surface than the wild-type strain, being less adhesive to polystyrene plates, reducing the biofilm formation (Kadry et al, 2018). He et al (2018) evaluated the role of α-1,3-glucan, a primary cell wall component in many filamentous fungi, including in A. nidulans biofilm formation. The overexpression of α-1,3-glucan synthase in A. nidulans triggered a higher cellular adhesion to hydrophobic materials and biofilm formation than the wild-type strain, which could contribute to fungal virulence (He et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from that, we and other groups found that α-glucan is critical for conidial adhesion ( 3 , 4 , 10 ). Artificial overexpression of α-glucan in Aspergillus nidulans could trigger cell wall reconstitution and thus promote fungal cell adhesion and biofilm formation ( 11 ).…”
Section: Introductionmentioning
confidence: 99%